Optimization Operation of Water Resources Using Game Theory and Marine Predator Algorithm - Far, Shirin Moradi; Ashofteh, Parisa-Sadat (Water resources management, 2024)
Today, one of the most important issues in the field of common water resources management is the allocation of water resources to different stakeholders with different interests. Game theory and conflict resolution methods, taking into account the interests and strategies of the players, provide efficient methods for allocating reservoirs water resources to stakeholders. In this research, for the first time, a wide range of different methods of game theory are used in order to allocate the water resources of Idoghmosh Dam reservoir (East Azarbaijan—Iran) to the agricultural and environmental stakeholders in the downstream. For this purpose, the NASH and four methods of bankruptcy theory, including PRO, AP, CEA, and CEL are used in this research. Also, in this research, the dam component is considered as a player. In the presented model for the optimal allocation of water to consumers, for the first time, the combination of game theory and the MPA as main innovation of this study is used, and the results obtained from it are compared with the GA. The proposed model is used in the base period (1987–2000) and the 14-year climate change period (2026–2039). In the following, for the first time, a wide range of different efficiency indexes of reliability, resiliency, vulnerability, flexibility, availability, supply to demand, volume reliability and SSD are used to analyze the reservoir operation policies. The results show that for each agricultural and environmental player in different base and future periods, the performance of different game theory methods on different indexes has been different. For example, the results for the agricultural player in the future period show that MPA with PRO method and then AP provided the best results for the indexes of vulnerability, resiliency, reliability, SSD , and supply to demand, that the similar values provided using GA and other bankruptcy methods have assigned lower values than MPA.